Controlled glycosylation of therapeutic antibodies in plants. - Tekoah, Y; Ko, K; Koprowski, H; Harvey, D; Wormald, M; Dwek, R; Rudd, P (2004)
Recombinant therapeutic monoclonal antibodies (mAb) can be expressed, assembled, and glycosylated in plants. Transgenic plants, producing anti-rabies mAb and anti-colorectal cancer mAb, were obtained from Agrobacterium-mediated transformation. The heavy chain (HC) of anti-rabies mAb was fused to the Lys-Asp-Glu-Leu (KDEL) endoplasmic reticulum retention signal whereas the HC of anti-colorectal cancer mAb was not fused to the KDEL sequence. Gel release of glycans and detection by high-performance liquid chromatography (HPLC), together with computer assisted analysis and matrix-assisted laser desorption/ionization time-of-flight (MALD-TOF) mass spectrometry, revealed that the plant-derived anti-rabies mAb with KDEL contained mainly oligomannose type N-glycans while the plant-derived anti-colorectal cancer mAb carried mainly biantennary glycans with and without a pentose sugar, that is thought to be xylose. This finding indicates that the KDEL sequence can affect the N-glycosylation processing of antibody in plant cells. The plant-derived mAbs with addition of a KDEL sequence did not contain any of the known antigenic glycan epitopes that are frequently found in other plant glycans or in mammalian-derived mAbs. The altered glycosylation on both plant-derived mAbs did not affect the activities that are required for therapy. These results indicate that plant genetic engineering could provide an effective and inexpensive means to control the glycosylation of therapeutic proteins such as mAbs, by the addition of a KDEL signal as a regulatory element.